Pattern of Congenital Anomalies among Pediatric Surgical Patients in Bangladesh - K M Zafrul Hossain; Md Mijanur Rahman; Md Jahangir Alam; Md Hasan Ullah; Md Safwanur Karim Sakib; Shamema Sultana (Pediatric Review: International Journal of Pediatric Research, 2025)
Background:Congenital anomalies are structural or functional abnormalities present from intrauterine life, contributing significantly to neonatal morbidity and mortality, especially in low- and middle-income countries. These conditions often require early surgical intervention, yet limited diagnostic and treatment facilities hinder timely care. Common anomalies in pediatric surgery include gastrointestinal malformations, neural tube defects, and abdominal wall defects.Methods:This hospital-based cross-sectional descriptive study was conducted over one year at the Department of Pediatric Surgery, TMSSMedical College Hospital and Private Camber, Bogura, Bangladesh from January to December 2024. A total of 135 pediatric patients (aged 0–5 years) with structural congenital anomalies requiring surgical evaluation were selected through purposive sampling from (start) to (end). Data were collected via structured interviews with guardians, clinical examinations, antenatal records, and surgical findings. Variables included demographics, obstetric history, anomaly type, surgical interventions, and outcomes. Patients with acquired anomalies or incomplete data were excluded. Data were analyzed using SPSS version 26.0, with results summarized using descriptive statistics and presented in tables.Result:The study revealed that most pediatric patients with congenital anomalies were aged 1–5 years (33.33%) or neonates (29.63%), with a male predominance (62.96%). Normal vaginal delivery was more common (59.26%), and antenatal detection of anomalies was low (18.52%). Anorectal malformation (22.22%) was the most frequent anomaly, followed by cleft lip/palate (14.81%) and neural tube defects (11.11%). Surgical intervention was required in 81.48% of cases, mostly elective. Postoperative complications occurred in 14.81%, and 70.37% had favorable outcomes. However, 11.11% faced complications, another 11.11% were referred, and 3.70% died. The findings highlight the need for improved prenatal diagnosis and early intervention.Conclusion:The study reveals a high burden of congenital anomalies in Bangladeshi pediatric surgical patients, notably anorectal malformations, cleft lip/palate, and neural tube defects. Most required early surgery. Limited antenatal detection and notable complications highlight the urgent need for improved prenatal screening, early diagnosis, and strengthened pediatric surgical care.